Corporate Social Responsibility in Light of the Corona Pandemic: Experiences of leading international companies according to the Corporate Social Responsibility Magazine for the year 2021 - djemadi, Monira (Finance and Business Economies Review, 2023)
The purpose of this research is to identify the fact of the social responsibility of 6 companies, listed among the top 30 leading global companies according to the ranking of the Journal of Corporate Social Responsibility (CSR) 2021, through their various activities, which contributed to the service of individuals and communities, and the reduction of environmental impacts and epidemics, such as the new Coronavirus pandemic (COCVID-19). One of the most important results from this study is the tendency of global companies to adopt social responsibility as an effective measure in the face of the negative effects of the Corona pandemic, although its deep consequences on these companies, governments, and societies all over the world. Based on that, this study recommended a set of suggestions, one of the most of them, is the requirement for national and Arab companies to focus on the priority of applying the dimensions of social responsibility because of its significant positive impact in overcoming the impact of the Corona pandemic; and developing businesses, economies, and societies.